Penerapan Regresi Kuadrat Terkecil Berbatas pada Pendugaan Fungsi Produksi Cobb-Douglas - Sadik Ikhsan; Pahriana Rahmawati (Universitas Lambung Mangkurat, 2012)
This research aimed to estimate and analyse Cobb-Doglas production function of paddy farming and to evaluate return to scale of production, as well as to apply least square regression restricted by constant return to scale (CRTS) assumption. The results of estimation and analysis by unrestricted least square regression was statistically unsatisfactory. Some factors of production i.e. chemical and organic fertilizer as well as chemical pesticide were not significant. Moreover, chemical pesticide had negative elasticity of production which was implied negative marginal product and, thereby, meaning that the factor of production was overutilized and had negative effect to paddy production. Introducing restriction of CRTS assumption to Cobb-Doglas production function had considerably improved the results in three things. Firstly, the existence of restriction was significant so that it was no doubt about the restriction. Secondly, all factors of production were exhibited statistically significant meaning that they had important influences to paddy production. Thirdly, the elasticity of production of all factors of production were positive and less than one. It implied that the utilizing of those factors of production were in the stage II of neoclassical production function where it was more favourable choice to operate the production operation in terms of profit maximization.